HUBUNGAN PENGETAHUAN PETUGAS KESEHATAN TENTANG INFEKSI SILANG DENGAN PENATALAKSANAAN PENCEGAHAN INFEKSI DI PUSKESMAS GUNTUNG MANGGIS KOTA BANJARBARU - Lailatus Sa’adah; Fahmi Said; Siti Salamah (JURNAL TERAPIS GIGI DAN MULUT, 2021)
Infectious diseases related to health services are one of the health problems in various countries in the world, including Indonesia. Judging from the origin of the infection, it can come from the community (Community Acquired Infection) or the health service environment or clinic. The highest case data in 2019 & 2020 at the Guntung Manggis Health Center were ISPA 3070 patients, cough and cold 1728 patients, pharyngitis 1314 patients, skin diseases 121 patients, & scabies 112 patients, these incidence rates indicate that health workers are susceptible to infection and contracting a disease. The purpose of this study was to determine the relationship between the knowledge of health workers about cross infection with the management of infection prevention at the Guntung Manggis Public Health Center, Banjarbaru City. The research method is an analytical survey with a cross sectional approach design. Sampling by purposive sampling with a total of 30 health workers from 43 populations. Collecting data using questionnaires and observation. The results showed that most of the knowledge of cross-infection was in the good category (60%) and the management of infection prevention was in the appropriate category (83.3%). Based on the Chi-Square test resulting in a p value of sig (2-sided) = 0.001 in the test, it can be concluded that the p value (probability value) of the test (p = 0.001 < = 0.05). The conclusion of this study is that there is a relationship between the knowledge of health workers about cross-infection and the management of infection prevention. It is recommended that this research can be input, especially for health workers and health service providers.Keywords: Knowledge-Health Officer-Cross-Infection